Strengthening groundwater governance in Pakistan - Rana, Abdul Wajid; Gill, Sitara; Meinzen-Dick, Ruth S.; ElDidi, Hagar (International Food Policy Research Institute, 2024)
Pakistan is highly dependent on irrigated agriculture for employment, income generation and food security—around 90 percent of all food production relies on either surface or groundwater irrigation. The growing dependence of agriculture but also industries and the drinking water sector on groundwater has led to the overexploitation of groundwater resources and, in some areas, to the deterioration of groundwater quality. Fiscal incentives for solarization of irrigation/drinking water pumps are likely to further increase water withdrawals and make water governance more complex. To understand the perspectives of groundwater users, a qualitative study was conducted in the alluvial groundwater systems of Punjab as well as the hard rock systems of Balochistan. Interviews with key informants at federal, provincial, and district level were also conducted to capture insights from additional decisionmakers affecting groundwater management and governance.